The Effect of Job Satisfaction and Organizational Commitment Towards Organizational Citizenship Behavior (OCB): A Case Study on Employee of Local Water Company "Tirta Mahakam" Kutai Kartanegara Indonesia - Iskandar, Iskandar; Hutagalung, Dedi Januar; Adawiyah, Raudatul (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to examine the influence of job satisfaction and organizational commitment towards organizational citizenship behavior. The study was a case study on employees of local water company "Tirta Mahakam" located in Kutai Kartanegara Regency. Quality of service will always be a significant factor for organizations that focus on customer satisfaction. It is done to improve business activity and organizational performance. To have excellent quality services depends on the human resources of the organization. The organization needs human resources that are performing well. Human resources/employees who show strong OCB are believed to be able to perform better. That is why organizations need to create employees with strong OCB. This study was a causal associative study using a quantitative approach. Data were collected using a closed questionnaire with a total sample of 83 respondents, and the selection of respondents chosen using simple random sampling. The results showed that job satisfaction and organizational commitment simultaneously affected organizational citizenship. Job satisfaction partially influenced organizational citizenship behavior. Organizational commitment partly influenced organizational citizenship behavior. Job satisfaction was proven to have the most significant influence.